Moving Forward : Connectivity and Logistics to Sustain Bangladesh’s Success - World Bank (World Bank, Washington, DC, 2019)
Bangladesh has been successful on many counts. The economy grew six percent a year between 2000 and 2017, and the poverty rate fell by more than half. All sectors experienced growth, but the contribution of agriculture to gross domestic product (GDP) declined, as Bangladesh became an important player in the textile and ready-made garments global value chain, which accounts for more than half of manufacturing employment and eighty-four percent of all exports in the country. The sustainability of this growth model is now being challenged, as Bangladesh’s competitiveness based on low wages is eroding. Rising wage demands from workers, intensifying global price competition, and inefficient logistics are putting significant cost pressure on Bangladeshi producers. This report presents a comprehensive assessment of logistics performance, its root causes, and the economic implications of potential interventions. Based on the analysis, the report proposes policy directions to improve logistics performance